Chromatographic separation and identification of a water-soluble dendritic methano[60]fullerene octadecaacid - Gharbi, Najla; Burghardt, Stephan; Brettreich, Michael; Herrenknecht, Christine; Tamisier-Karolak, Sara; Bensasson, René V.; Szwarc, Henri; Hirsch, Andreas; Wilson, Stephen; Moussa, Fathi (Analytical Chemistry, 2003)
The chromatographic separation of a highly water-soluble dendritic monoadduct methanol 60]fullerene octadecaacid (dendrofullerene) with octadecylsilica bonded phases has been studied. It has been found that the RP-HPLC behavior of this dendrofullerene obeys the general rules of stationary-phase and mobile-phase selection for controlling the separation of usually acidic compounds. An RP-HPLC-ESI-MS analysis confirms the identity of the dendrofullerene and allows characterization of the molecular weights of the main impurities contained in the sample. The described methods can control the synthesis and efficiently purify this fullerene derivative, which has been previously shown to be active against mutant infectious clones of HIV-1, which are resistant to AZT and 3TC, drugs that are widely used in AIDS therapy.